2022
DOI: 10.1016/j.crfs.2021.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L.plantarum dy-1 fermentation time on the characteristic structure and antioxidant activity of barley β-glucan in vitro

Abstract: This article explored the effect of Lactobacillus plantarum dy-1 (L. plantarum dy-1 ) fermentation on the basic physicochemical properties and associated in vitro antioxidant activity of barley β-glucan, including its molecular weight, monosaccharide composition, characteristic structure and rheology. Its DPPH, ABTS, hydroxyl radical scavenging capacity, and ferric reducing antioxidant potential (FRAP) were measured at different fermentation times. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…An increase in antioxidant activity during fermentation was shown during the fermentation P. yezoensis with lactic acid bacteria (Yang et al ., 2022). But, the fermentation of β‐glucan with Lactobacillus planetarium did not change significantly antioxidant capacity (Zhang et al ., 2022). According to this study, barley β‐glucan hydrolysate, contained mainly 3‐O‐β‐cellobiosyl‐D‐glucose and minor 3‐O‐β‐cellotriosyl‐D‐glucose, and was 30.9% more effective at DPPH activity than untreated β‐glucan after 1 h of hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…An increase in antioxidant activity during fermentation was shown during the fermentation P. yezoensis with lactic acid bacteria (Yang et al ., 2022). But, the fermentation of β‐glucan with Lactobacillus planetarium did not change significantly antioxidant capacity (Zhang et al ., 2022). According to this study, barley β‐glucan hydrolysate, contained mainly 3‐O‐β‐cellobiosyl‐D‐glucose and minor 3‐O‐β‐cellotriosyl‐D‐glucose, and was 30.9% more effective at DPPH activity than untreated β‐glucan after 1 h of hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study showed that the M w of barley β-glucan was significantly decreased from 5.14 × 10 5 kDa to 4.97 × 10 4 kDa, while the monosaccharide composition and the glycosidic bond ratio changed significantly after being fermented with L. plantarum dy-1, which was possibly caused by the glucanase in L. plantarum dy-1. 5,24 Disruption of the surface of The crude enzyme was secreted by the recombinant strain and the purified enzyme was purified by Ni-column affinity. Food & Function Paper barley bran by enzymatic hydrolysis with endoglucanase enables the release of bioactive ingredients, such as the combined polyphenols, which may further improve the physiological function of the bran.…”
Section: Effect Of Enzymatic Hydrolysis By Lpeg14265 On the Structure...mentioning
confidence: 99%
“…5 The bioassay of our previous study revealed that β-glucan in fermented barley exhibited increased inhibitory capacity of amylase, glucosidase and lipase, indicating that fermentation by L. plantarum dy-1 could improve physiological activities of β-glucan in barley in vitro, especially involving glucose and lipid metabolisms. 24,28 The improved physiological activity of β-glucan may be ascribed to the key role of endoglucanase secreted during the fermentation of barley.…”
Section: Effect Of Enzymatic Hydrolysis By Lpeg14265 On the Structure...mentioning
confidence: 99%
“…The importance of these macromolecules is related to the interesting activities that they can exert, highlighting the capability of modulating the immune system and exerting hypoglycemic and hypolipidemic effects, particularly reducing serum cholesterol levels [ 4 , 5 , 6 ]. Moreover, technological functionalities can be also exploited, since antioxidant and antimicrobial activities of β-glucans might be used in food preservation and their gelling properties have been applied, for instance, to develop easy-to-swallow products for elderly people [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%